A Study on the Deposition of Tin on the Contac ts Subjected to High Frequency Impac t Loading in Semiconductor Device Testing - Ong, K.Y.; SAID, MD RADZAI (Penerbit UTeM, 2011)
Semiconductor device leads were previously plated with Lead (Pb). Due to environmental concern, the plating material has been switched to Tin (Sn). However, due to the softness of Tin element plating, it often wears off and its residues deposited to the surface of the contacts used in semiconductor device testing. As a result, significant drop of contact performance has been observed. This study intends to find out a theoretical explanation to the problem of tin deposition. As soon as the root cause is identified, studies go into the details of how to solve this problem. One of the economical suggestions is to apply lubricants on the contact. A theoretical calculation is derived to verify if the lubricant would significantly altered the overall resistance.